STUDY ON THE REFORMATIVE IMPACT OF DIGITAL MARKETING AND DEMOGRAPHIC FACTORS ON COSMETIC BUYING BEHAVIOUR OF MALE CONSUMER - et. al., Akanksha Dhiman (International Journal of Modern Agriculture, 2021)
Purpose – To understand the impact of digital marketing factors such as interaction and electronic word of mouth as well as their relationship with demographic factors such as income and age to influence the male consumer behaviour towards the cosmetics. Design/Methodology/Approach – The research conducted is descriptive in nature. The collection of data involves the structured questionnaire and data analysis with appropriate statistical tools. The sample respondents were selected using Simple Random Sampling, the data was collected from the 200 targeted respondents in the cosmetic market, specifically male consumers in India. Findings – Cosmetic giants in India are using digital marketing that is changing male consumer’s choices and buying behaviour. Secondary data gathered from various journals, research papers and articles also clearly reveals that digital marketing and demographic factors have highly influenced the cosmetic buying behaviour of the male consumer. Practical implications – Digital marketing effects male consumer buying behaviour towards cosmetic products and is also linked with their demographic factors. Originality/value – Adding value to the digital platforms of cosmetic industries, improve the target reach and understand the key strategies that can be adopted with the help of these key factors that majorly impact the male consumer behaviour.